2023
DOI: 10.1101/2023.04.10.23288368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Hospital Readmission among Patients with Sepsis using Clinical and Wearable Data

Abstract: Sepsis is a life-threatening condition that occurs due to a dysregulated host response to infection. Recent data demonstrate that patients with sepsis have a significantly higher readmission risk than other common conditions, such as heart failure, pneumonia and myocardial infarction and associated economic burden. Prior studies have demonstrated an association between a patient's physical activity levels and readmission risk. In this study, we show that distribution of activity level prior and post-discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While the causal mechanism is unknown, LEP is known to be associated with greater difficulties in accessing medical care, and language barriers can impede providers' ability to take an appropriate clinical history that may lead to clinical errors or delays in care. In our previous work, we have demonstrated that SDoH (8) and wearable (9,10) data can dramatically improve the accuracy of sepsis readmission scores. However, SDoH factors are often poorly captured in electronic health records (EHRs) and are not available at the time of hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…While the causal mechanism is unknown, LEP is known to be associated with greater difficulties in accessing medical care, and language barriers can impede providers' ability to take an appropriate clinical history that may lead to clinical errors or delays in care. In our previous work, we have demonstrated that SDoH (8) and wearable (9,10) data can dramatically improve the accuracy of sepsis readmission scores. However, SDoH factors are often poorly captured in electronic health records (EHRs) and are not available at the time of hospital discharge.…”
Section: Introductionmentioning
confidence: 99%